Prospects for X-Ray and FUV Observations to Provide Insight Into the “Cepheid Mass Problem” - Evans, Nancy Remage; Engle, Scott (Frontiers in Astronomy and Space Sciences, 2019)
The classical Cepheid Leavitt Law (Period-Luminosity relation) has been known for 100 years, and used as in extragalactic distance determination for nearly as long. However, Cepheids still present us with surprises. Recent results about X-ray behavior is just one example. Around minimum radius the pulsation wave from the envelope creates a disruption in the photosphere and chromosphere. X-ray activity, on the other hand remains constant at a low level at this phase. Just after maximum radius, however, X-ray flux increases sharply (four fold in the case of $δ$ Cep). We summarize here the observational program to explore parameters involved and theoretical investigations searching for a basic understanding of this upper atmosphere phenomena.